ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN DI PT. TELESINDO SHOP CABANG MANDREHE KABUPATEN NIAS BARAT TAHUN 2015-2019 - Fau, Samanoi Halowo; MANAO, ALWINDA (Balance: Jurnal Riset Akuntansi dan Bisnis, 2022)
The scope of this research is the study of the analysis of financial statements to assess the financial performance at PT. Telesindo Shop Mandrehe Branch of West Nias Regency 2015-2019. This research aims to find out the financial performance of PT. Telesindo Shop Mandrehe Branch of West Nias Regency 2015-2019 which is reviewed from the analysis of financial ratios namely liquidity, solvency and rentability ratios. Based on the results of the research conducted it can be known that the calculation of liquidity ratio with unfavourable results, which are reviewed from the current ratio, cash ratio and quick ratio obtained less good results for five years. Then the results of solvency ratios reviewed from the results of debt to asset ratio and debt to equity ratio get less good results. But if viewed from the calculation of the ratio of rentability seen from return on asset get good results because it is above the standard average of measurement. Similarly, the return on equity results gets good results.